“Estimación del índice de mérito total del programa de mejoramiento genético sostenible de bovinos de leche en la parroquia Mulaló”. - Calderón Quinaluisa, Neysser Ivan (2023)
The general objective of this research project was total merit index estimation of the sustainable genetic improvement program for dairy cattle in Mulaló parish, Latacunga canton, based on economically important traits. The research involved 87 animals and 11 producers who are part of the project. Data collection took place during April, May, and June months 2023, including production costs (with low reliability), GDP, production at 305 days, and density. Results for production costs showed an average of $0.09 in costs per liter of milk, with maximum values of $0.12 and minimum values of $0.06. The cost that represents the highest value is feed, accounting for 40% of the total costs. Regarding the database, the average monthly benefit of Mulaló parish is around $800, recognizing low reliability due to producers do not habitually maintain records. Consequently, production costs will appear very low, leading to unreliable decision-making. The genetic value (EBV) of each animal, in terms of GDP, estimates a maximum cutoff point of 70.9; the density reaches a maximum peak of 0.5, considering it will be added to the estimated average. Concerning lactation at 305 days, maximums peak reach 776.6. Estimating genetic value, it can be determined that planned objectives will be observed in future generations, approximately over 6 generations. The dominant production factor at 305 days is followed by GDP, with low density regarding future generations. Based on the recorded data from dairy production, the total merit index of genetic improvement program in Mulaló parish was estimated. This identified the best breeding specimens for the evaluation traits, including a Holstein breed named Muñeca for daily weight gain, a Red Swedish breed named Federica for milk production, and a Jersey breed named Café for milk density. All traits were linked to selection response.